The Effect of Corporate Social Responsibility, Company Size, and Capital Structure on Company Value - Sri Putri Winingrum W.A.; Ririn Fitrianita (J-CEKI : Jurnal Cendekia Ilmiah, 2026)
This study provides empirical evidence on the role of Corporate Social Responsibility, firm size, and capital structure in explaining firm value within the consumer non-cyclicals sector listed on the Indonesia Stock Exchange during the 2020–2024 period. A quantitative approach was applied using panel data comprising 220 firm-year observations obtained from 44 companies selected through purposive sampling. Panel regression analysis was employed, with model selection and classical assumption testing guiding the choice of the Random Effect Model as the most appropriate estimation technique. The empirical results demonstrate that Corporate Social Responsibility, firm size, and capital structure do not exert a statistically significant effect on firm value, either simultaneously or individually. These findings suggest that firm value in the consumer non-cyclicals sector is not directly driven by CSR disclosure levels, firm scale, or capital structure policies, but is instead influenced by other determinants beyond the scope of the variables examined in this study.